On drug treatment and social control: Russian narcology's great leap backwards - Elovich, Richard (BioMed Central, 2008)
The medical discipline of narcology in Russia is a subspecialty of psychiatry from the Soviet era and it is given warrant to define the scope of health activities with regard to alcohol and other drug use, drug users, and related problems. Narcological practice is in turn constrained by the State. The emergence of widespread injection opiate use and associated HIV morbidities and mortalities during the first decade following the collapse of the Soviet Union has brought the contradictions in Russian narcological discourse into high relief. Narcology officials in the Russian Federation have consistently opposed substitution treatment for opiate dependence – the replacement of a short-acting illegal substance with a longer acting prescribed drug with similar pharmacological action but lower degree of risk. Thus, despite the addition of methadone and buprenorphine to WHO's list of essential medicines in 2005 and multiple position papers by international experts calling for substitution treatment as a critical element in the response to HIV (IOM, 2006; UNODC, UNAIDS, and WHO, 2005), methadone or buprenorphine remain prohibited by law in Russia. The authors detail Russian opposition to the prescription of methadone and buprenorphine, describing four phenomena: (1) the dominance of law enforcement and drug control policy over public health and medical ethics ; (2) the conflation of Soviet era alcoholism treatment with treatment for opiate dependence; (3) the near universal representation of detoxification from drugs as treatment for dependence; and (4) a framework for judging treatment efficacy that is restricted to "cure" versus "failure to cure," and does not admit its poor outcomes or recognize alternative frameworks for gauging treatment of opiate dependence. In keeping with this position, Russian narcology officials have taken an implacable ideological stance toward illicit drug use, the people who use drugs, and their treatment. By adopting policies and practices totally unsupported by scientific evidence and inquiry, officials in Russia have rendered narcology ( and medical practice) insensitive to the alarming rates and continued spread of HIV, with its dire morbidity and mortality rates in the Russian Federation, turning their backs on all the other health problems posed by opiate use and dependence itself.